PENGARUH KEPEMILIKAN INTERNAL, KUALITAS AUDIT DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Zumrotun Nafiah; Sopi Sopi (JURNAL STIE SEMARANG, 2020)
Establishment of a company has a clear goal one of which is to maximize the firm value. There are many factors affecting firm value and this study intends to empirically learning the effect of internal ownership, audit quality, and debt policy to firm value. The population of this study is manufacturing companies listed on the Indonesian Stock Exchange for period 2017-2019, amounting to 149 companies. The sample of the study was selected as many as 11 companies with purposive sampling technique. Data collection method of this research is documentation. Data were analyzed using statistical decriptive and multiple regression analysis. The result shows that there is no positive influence of internal ownership to firm value with p=0.552 (p>0.05), audit quality has significant effect to company value with p=0.035 (p<0.05), debt policy has no significant effect on the firm value with p=0.807 (p> 0.05). The next study must adding other variables that also could affect the firm value such as leverage, profitability, investment, institutional ownership and others